A great disorder : national myth and the battle for America - Slotkin, Richard, 1942- (The Belknap Press of Harvard University Press, 2024)
"Red America and Blue America are so divided they could be two different countries, with wildly diverging views of why government exists and who counts as American. Their ideologies are grounded in different versions of American history, endorsing irreconcilable visions of patriotism and national identity. A Great Disorder is a bold, urgent work that helps us make sense of today's culture wars through a brilliant reconsideration of America's foundational myths and their use in contemporary politics. Famous for his trilogy on the Myth of the Frontier, Richard Slotkin identifies five myths, born of different eras, that have shaped our conception of what it means to be American: that of the Frontier, the Founding, the Civil War (which he breaks into two opposing camps, Emancipation and the Lost Cause), and the Good War, embodied by the multi-ethnic platoon fighting for freedom. Slotkin's argument is that while Trump and his MAGA followers have played up a frontier-inspired hostility to the federal government and rallied around Confederate symbols to champion a racially exclusive definition of American nationality, Blue America, taking its cue from the protest movements of the 1960s, envisions a limitlessly pluralistic country in which the federal government is the ultimate enforcer of rights and opportunities. American history -- and the foundations of our democracy -- have become a battleground. It is not clear at this time which vision will prevail." --